The role of gut microbes in drought adaptation in the five-toed jerboa (Orientallactaga sibirica) - Haoting Zhang; Dongyang Chu; Haiwen Yan; Shanshan Sun; Xiaodong Wu; Heping Fu; Shuai Yuan (BMC Microbiology)
Abstract The composition of the gut microbiota of animals is closely linked to host health and environmental adaptability. It can increase the phenotypic plasticity of animals, thereby improving their ability to thrive in harsh environments. The five-toed jerboa (Orientallactaga sibirica) is widely distributed in various regions, particularly in western Inner Mongolia and Xinjiang, which are located in the arid western part of China, and is capable of tolerating an arid environment. However, the relationships between the five-toed jerboa’s adaptation to such conditions and its gut microbiota have not yet been studied. In this study, we aimed to investigate the relationships between the gut microbiota of the five-toed jerboa and their adaptations to drought and water scarcity. Five-toed jerboa individuals were subjected to two treatments: water deprivation (experimental group, EG) and normal drinking water intake (control group, CG). Fecal samples from both groups were collected for sequencing and analysis of the V3-V4 variable region using 16 S rRNA. The results indicated that while the microbial composition is similar, there are differences in the relative abundance of microbes. The dominant bacteria in both groups were Firmicutes and Bacteroidota. The relative abundances of various genera within the bacterial community were significantly altered, with the abundance of Lactobacillus being most affected. The alpha diversity of the gut microbiota significantly differed between the EG and CG on the 5th and 11th days of water stress, with the EG showing significantly greater diversity than the CG (ACE, Chao and Shannon index) (P < 0.05). PICRUSt prediction revealed that the abundance of metabolism-related genes remained relatively consistent in the CG; however, in the EG, the abundance of genes associated with metabolism and cellular processes increased as the duration of stress increased. The five-toed jerboa adapted to water stress conditions by increasing the abundances of short-chain fatty acid-producing bacterial genera and altering the diversity of its gut microbiota. The results of this study suggest that five-toed jerboa may adapt to arid and water-scarce environments by increasing the abundance of beneficial bacteria in their gut microbiota.